Dual activity cavitation reactors for increased efficacy in degradation of refractory pollutants-A case study on cephalexin degradation - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2023)
The present work discloses a new form of cavitation processes using reactors of dual activity for increased efficiency. A proof of concept is established for the degradation of a refractory pollutant-cephalexin using both conventional and dual function cavitation reactors for the first time using acoustic and hydrodynamic cavitation (HC). A vortex diode as a cavitating device was employed for HC using aluminium as a non-catalytic and copper as dual function device for providing additional catalytic effect. The process in-tensification using hydrogen peroxide (H2O2) coupled with the dual function devices was highly effective. A negligible degradation with only HC and 81% for HC coupled with H2O2 in 60 min for Al-vortex diode compared to 100% degradation in only 5 min for the copper device clearly demonstrates the order of magnitude enhancements establishing dual function due to catalytic activity. Also, pH modification (pH 11) yields enhancement over 300% for Cu-vortex diode. The use of dual function reactors drastically reduces H2O2 do-sage. The overall enhancements in the per pass degradation and cavitation yields were huge, similar to 3000% and 1450% respectively, highlighting the potential of the dual function ca-vitation reactors in real-life applications, not just for increased efficiencies but also for significantly reduced costs.(c) 2023 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Advanced oxidation; Degradation; pollution; Technology; Wastewater treatment

Enhanced degradation of metformin using surface-coated vortex diodes - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical engineering and processing-process intensification, 2023)
The present work successfully demonstrates, for the first time, complete degradation of metformin using newer surface-coated vortex diode (SCVD) with copper and nickel coating to provide catalytic activity in the conventional hydrodynamic cavitation (HC) for significantly enhanced degradation efficiency. The SCVDs have dual functionality and the efficacy of catalytic cavitation reactors get enhanced using process intensifications of the type H2O2 addition, pH modification, and combined approach of HC+ pH+ H2O2 apart from the advantage of low pressure drop for the vortex flow based cavitation in vortex diode (Delta P of 1 bar). Complete, 100%, degradation of metformin (MTF) was achieved within 5 min with integration of optimized H2O2 dose and exceptionally high synergistic index value over 300, indicating extraordinary synergy for both Cu and Ni-SCVD. Acidic condition promote degradation and a complete degradation with a high 43-48% mineralization was observed using HC+ pH 4+ (1:200) H2O2 with less intermediates formation. The SCVDs reveal remarkable enhancement of similar to 9800% in per-pass degradation and 1400-3400% in cavitational yield as compared to conventional cavitation process under similar conditions. The newer SCVDs with catalytic activity can provide more cost-effective solutions for industrial and real-life applications.
Keywords: Cavitation; Oxidation; pollution; Technology; Wastewater treatment

Improving hydrodynamic cavitation using newer surface-coated cavitation reactors - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2023)
Surface-coated cavitation devices, vortex diode (SCVD) have been reported for the first time for enhancing efficiency of hydrodynamic cavitation (HC). Two surface-coated cavitation reactors using coating of copper and nickel (-50 mu m) were evaluated, also comparing results with conventional reactor vortex diode. The proof of concept is successfully demonstrated for complete degradation of two model organic pollutants, antibioticscephalexin (CFX) and ciprofloxacin (CIP). The surface-coated reactors provide dual activity, and the catalytic effect is highly pronounced with process intensification using H2O2 and/ or pH alternations. Integration of SCVD, pH and H2O2 was the most effective strategy. Complete degradation of the antibiotics was achieved within minutes with H2O2 (-1000 molar ratio) for both Cu and Ni-surface-coated cavitation reactors compared to lower degradation of-19% for CFX and-37% for CIP using only HC. An excellent enhancement of over 300% for CFX degradation at pH 11 and-170% for CIP degradation at pH 4 was obtained. Huge enhancements in per-pass degradation and cavitational yields (up to 400 times) clearly highlight the utility of the surface-coated cavitation reactors in various applications and for cost-effectiveness.(c) 2023 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrodynamic cavitation; Oxidation; pollution; Reactor; Technology; Wastewater treatment